1999
DOI: 10.1016/s0014-5793(99)00405-6
|View full text |Cite
|
Sign up to set email alerts
|

The non‐enzymatic microbicidal activity of lysozymes

Abstract: T4 lysozyme was thought to destroy bacteria by its muramidase activity. However, we demonstrate here that amphipathic helix stretches in the C-terminus of T4 lysozyme mediate its bactericidal and fungistatic activities. In heatdenatured T4 lysozyme, the enzymatic activity is completely abolished but unexpectedly, the antimicrobial functions remain preserved. Small synthetic peptides corresponding to amphipathic C-terminal domains of T4 lysozyme show a microbicidal activity. Its membrane disturbing activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(187 citation statements)
references
References 22 publications
8
176
1
2
Order By: Relevance
“…Synergistic effects may occur when one peptide in a conformation parallel to the bacterial membrane facilitates insertion of other peptides (63). We speculate that such an effect might account for synergistic activity between hBD-3 and LL-37 as well as synergism for the combination of LL-37 and lysozyme; in addition to its enzymatic activity, lysozyme has nonenzymatic antibacterial activity dependent on its cationic and hydrophobic domains that disrupt bacterial plasma membranes (64)(65)(66). A possibility that we cannot exclude is that variations in pH might render S. aureus and P. aeruginosa more or less susceptible to antimicrobial factors.…”
Section: Discussionmentioning
confidence: 96%
“…Synergistic effects may occur when one peptide in a conformation parallel to the bacterial membrane facilitates insertion of other peptides (63). We speculate that such an effect might account for synergistic activity between hBD-3 and LL-37 as well as synergism for the combination of LL-37 and lysozyme; in addition to its enzymatic activity, lysozyme has nonenzymatic antibacterial activity dependent on its cationic and hydrophobic domains that disrupt bacterial plasma membranes (64)(65)(66). A possibility that we cannot exclude is that variations in pH might render S. aureus and P. aeruginosa more or less susceptible to antimicrobial factors.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, the activity of the CfP1 phage seems to tolerate higher pH values better than the recombinant lysin, which indicates that other lytic accessory proteins might have an important role in phage antibacterial activity. The ability of a Gram-negative-specific phage lysin to kill cells Bfrom without^has been solely attributed to few enzymes (e.g., Enterobacter phage T4, Bacillus phage PlyL, Acinetobacter phage PlyF307, and Pseudmonas phage OBP lysins) (During et al 1999;Morita et al 2001;Walmagh et al 2012;Lood et al 2015). This effect was associated to the positively charged amino acids located at the enzyme's Ctermini, which is able to disrupt or mediate lysin access to the peptidoglycan, causing subsequent bacteriolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concept of muramidase-independent killing of bacteria continues to be debated (27), there is increasing evidence in support of this hypothesis (20,22,28,29). Recent studies identified a bactericidal domain that mapped to the C-terminal region of chicken and human lysozyme (30).…”
Section: Lysmmentioning
confidence: 99%